(untitled) (Journal of Medicine, 2024)
Background: The sudden shift to remote learning, prompted by global health restrictions, compelled educators to devise innovative pedagogical strategies that transcend traditional boundaries. This transition underscored the pivotal role of technology in bridging gaps and enhancing learning experiences. As a result, technology ceased to be a mere supplement and instead became an essential conduit for effective medical education delivery. Methods: A systematic review was performed by searching relevant studies until June 2023 using the PubMed, MEDLINE, and EMBASE databases. The sudden shift to remote learning, prompted by global health restrictions, compelled educators to devise innovative pedagogical strategies that transcend traditional boundaries. This transition underscored the pivotal role of technology in bridging gaps and enhancing learning experiences. As a result, technology ceased to be a mere supplement and instead became an essential conduit for effective medical education delivery. Results: The systematic review of the literature found 47 studies that satisfied the inclusion criteria, addressing different facets of technology’s influence on medical education during the post-COVID-19 pandemic period. The analysis reveals a dynamic landscape where challenges catalyzed advancements. Educational institutions swiftly adapted to the new normal by embracing technology-driven solutions. Virtual patient interactions, augmented reality modules, and AI-driven personalized learning emerged as effective tools. These innovations not only addressed immediate challenges but also laid the groundwork for a more flexible and inclusive medical education ecosystem. Conclusions: The challenges experienced throughout the COVID-19 pandemic have significantly influenced the transformation of medical education in the post-pandemic era. By analyzing challenges and proposing innovative solutions, the crucial significance of technology is underscored, emphasizing the necessity for a comprehensive and adaptable approach to shape the trajectory of future medical education. J MEDICINE 2024; 25: 166-172